(untitled) - Saxena, Sangeeta; lal, Bhajan; Meena, Dharm Raj; Vardhan, Harsh; Gupta, Abhishek; Godara, Chandraveer Singh (Asian Journal of Medical Radiological Research, 2019)
Background: MRI is now the preferred imaging modality and preferred technique to define the activity and extent of infection for patients with suspected spinal tuberculosis. The objective of the study was to describe diagnostic accuracy, sensitivity and specificity of MRI in diagnosis of spinal tuberculosis and various radiological features of spinal tuberculosis (TB) on magnetic resonance imaging (MRI). Subjects and Methods: Out of total 45 cases of suspected tuberculosis in our study we given 38 case as spinal spondylo-discitis out of which 36 cases accurately diagnosed by MRI proved by histopathology or culture reports. And 7 cases of given non tubercular out of which 1 case came to be tubercular spondylodiscitis on histopathology. MRI case records of these 37 patients with proven tuberculosis retrospectively analysed. Results: The majority of the patients were males 60% (22/37) and most common age group is 31 to 50 years age group (45%). The most common clinical presentation was backache 81% (n=30) followed by fever 22/37 cases (59.45%). The Thoraco-lumbar spine was the commonest site of the disease (38.64%) followed by the lumbar region (31.82%). An intervertebral disc involvement, pre and paravertebral collections, subligamental extension of the abscess were commonly seen, with an epidural collection occurring in more than 75 % of the cases. In addition few cases also showed single vertebral involvement (n-3) and few cases shows skip lesions. Conclusion: The MRI scan is highly sensitive in the detection of various pathological processes of spinal tuberculosis and their pattern of occurrence. The extent of soft tissue involvement disease is best assessed by MRI which help in guiding the surgical treatment as well as to monitor the response to treatment during follow up.